Correlations between the simulated military tasks performance and physical fitness tests at high altitude - Neves, Eduardo Borba (2017)
The aim of this study was to investigate the Correlations between the Simulated Military Tasks Performance and Physical Fitness Tests at high altitude. This research is part of a project to modernize the physical fitness test of the Colombian Army. Data collection was performed at the 13th Battalion of Instruction and Training, located 30km south of Bogota D.C., with a temperature range from 1ºC to 23ºC during the study period, and at 3100m above sea level. The sample was composed by 60 volunteers from three different platoons. The volunteers start the data collection protocol after 2 weeks of acclimation at this altitude. The main results were the identification of a high positive correlation between the 3 Assault wall in succession and the Simulated Military Tasks performance (r = 0.764, p<0.001), and a moderate negative correlation between pull-ups and the Simulated Military Tasks performance (r = -0.535, p<0.001). It can be recommended the use of the 20-consecutive overtaking of the 3 Assault wall in succession as a good way to estimate the performance in operational tasks which involve: assault walls, network of wires, military Climbing Nets, Tarzan jump among others, at high altitude.